Social and environmental determinants of disease uncertainty in obstructive sleep apnea: a dyadic qualitative study on patients and co-residents - Niu, Yuqi; Shao, Yefan; Chen, Linlin; Wang, Yali; Sun, Shanwen; Zhang, Xiaochun (Frontiers in Neurology, 2025)
BackgroundObstructive sleep apnea (OSA) is a prevalent sleep disorder characterized by upper airway obstruction during sleep, leading to significant health issues and reduced quality of life. Despite its increasing prevalence, particularly among middle-aged and older adults, low awareness and treatment rates contribute to a substantial burden of disease uncertainty for both patients and their co-residents. This study aims to investigate the social and environmental determinants of disease uncertainty experienced by OSA patients and their co-residents, focusing on the impact of these factors on health behaviors and access to care.MethodsThe study employed the theoretical model of disease uncertainty as a guiding framework and utilized the KJ method for data analysis. Using purposive sampling, 13 OSA patients and their 13 co-residents were selected to form dyads. Ethical approval was obtained, and informed consent was secured from all participants prior to the study.ResultsThe analysis of the interview data yielded seven major themes and 19 sub-themes. (1) “The Shadow of Knowing Little”; (2) “The Fog of Night and Day”; (3) “Symbiotic Suffering”; (4) “The Hidden Costs”; (5) “Delay in Seeking Medical Care”; (6) “Complex Choices”; (7) “Vacancies Calling for Attention.”ConclusionThe findings underscore that OSA patients and their co-residents face considerable uncertainty related to disease awareness, symptom experiences, medical decision-making, treatment plans, and social support. This uncertainty leads to delays in seeking care and poor treatment adherence. To mitigate these issues, it is recommended to enhance public health education on OSA, improve disease awareness and self-management skills among patients and their families, and better integrate medical resources and social support networks. These interventions should address the social and environmental determinants of health to reduce the burden of disease uncertainty and improve overall health outcomes.